N-[4-(3-Methyl-3-phenyl-cyclobutyl)-thiazol-2-yl]-N'-pyridin-2-ylmethylene-chloro-acetic acid hydrazide: Synthesis and configurational assignment based on X-ray, 1H, and 13C NMR and theoretical calculations - Demir, Sibel; Dincer, Muharrem; Cukurovali, Alaaddin; Yilmaz, Ibrahim (Pleiades Publishing Inc, 2017)
In this study, quantum chemical calculations based on the density functional theory have been carried out to examine the effects of N-[4-(3-methyl-3-phenyl-cyclobutyl)-thiazol-2-yl]-N'-pyridin-2-ylmethylene- chloro-acetic acid hydrazide. The calculated values are compared with the experimental data available for these molecules as a mean of validation of our proposed chemistry model. Aided by normal coordinate analysis and potential energy distributions, a confident vibrational assignment of all fundamentals is proposed herein. Additional support is given by H-1 and C-13 NMR spectra recorded with the sample dissolved in CDCl3 and by predicted chemical shifts at the B3LYP/6-31G(d)/6-311G+(d) levels obtained using the gauge-invariant atomic orbital method. The calculated HOMO and LUMO energies also confirm that the charge transfer occurs within the molecule. Thiazole-based compounds are potential storehouse for exploiting CH center dot center dot center dot O and CH center dot center dot center dot N hydrogen bonding interactions for molecular self-assembly.
Keywords: Molecular Electrostatic Potentials; Transition-Metal Complexes; Ab-Initio; Cu(Ii); Chemistry; Reactivity; Mechanism; Co(Ii)